Quantifying Discharge Medication Reconciliation Errors at 2 Pediatric Hospitals. Issue 4 (July 2021) - Morse, Keith E.; Chadwick, Whitney A.; Paul, Wendy; Haaland, Wren; Pageler, Natalie M.; Tarrago, Rod
Abstract : Introduction: Medication reconciliation errors (MREs) are common and can lead to significant patient harm. Quality improvement efforts to identify and reduce these errors typically rely on resource-intensive chart reviews or adverse event reporting. Quantifying these errors hospital-wide is complicated and rarely done. The purpose of this study is to define a set of 6 MREs that can be easily identified across an entire healthcare organization and report their prevalence at 2 pediatric hospitals. Methods: An algorithmic analysis of discharge medication lists and confirmation by clinician reviewers was used to find the prevalence of the 6 discharge MREs at 2 pediatric hospitals. These errors represent deviations from the standards for medication instruction completeness, clarity, and safety. The 6 error types are Duplication, Missing Route, Missing Dose, Missing Frequency, Unlisted Medication, and See Instructions errors. Results: This study analyzed 67, 339 discharge medications and detected MREs commonly at both hospitals. For Institution A, a total of 4, 234 errors were identified, with 29.9% of discharges containing at least one error and an average of 0.7 errors per discharge. For Institution B, a total of 5, 942 errors were identified, with 42.2% of discharges containing at least 1 error and an average of 1.6 errors per discharge. The most common error types were Duplication and See Instructions errors. Conclusion: The presented method shows these MREs to be a common finding in pediatric care. This work offers a tool to strengthen hospital-wide quality improvement efforts to reduce pediatric medication errors.